Formulation and Ex Vivo Evaluation of Ivermectin Within Different Nano-Drug Delivery Vehicles for Transdermal Drug Delivery - Eunice Maureen Steenekamp; Wilna Liebenberg; Hendrik J. R. Lemmer; Minja Gerber (Pharmaceutics)
Background/Objectives: Ivermectin gained widespread attention as the “miracle drug” during the coronavirus disease 2019 (COVID-19) pandemic. Its inclusion in the 21st World Health Organization (WHO) List of Essential Medicines is attributed to its targeted anti-helminthic response, high efficacy, cost-effectiveness and favorable safety profile. Since the late 2000s, this bio-inspired active pharmaceutical ingredient (API) gained renewed interest for its diverse therapeutic capabilities. However, producing ivermectin formulations does remain challenging due to its poor water solubility, resulting in low bioavailability after oral administration. Therefore, the transdermal drug delivery of ivermectin was considered to overcome these challenges, which are observed after oral administration. Methods: Ivermectin was incorporated in a nano-emulsion, nano-emulgel and a colloidal suspension as ivermectin-loaded nanoparticles. The nano-drug delivery vehicles were optimized, characterized and evaluated through in vitro membrane release studies, ex vivo skin diffusion studies and tape-stripping to determine whether ivermectin was successfully released from its vehicle and delivered transdermally and/or topically throughout the skin. This study concluded with cytotoxicity tests using the methyl thiazolyl tetrazolium (MTT) and neutral red (NR) assays on both human immortalized epidermal keratinocytes (HaCaT) and human immortalized dermal fibroblasts (BJ-5ta). Results: Ivermectin was successfully released from each vehicle, delivered transdermally and topically throughout the skin and demonstrated little to no cytotoxicity at concentrations that diffused through the skin. Conclusions: The type of nano-drug delivery vehicle used to incorporate ivermectin influences its delivery both topically and transdermally, highlighting the dynamic equilibrium between the vehicle, the API and the skin.